Rasionalitas Penggunaan Antibiotik Pada Pasien Anak Rawat Inap Dan Rawat Jalan di Rumah Sakit - Moudyana Lukman; Rezky Putri Indarwati Abdullah; Sri Wahyuni Gayatri; Shofiyah Latief; Nevi Sulvita Karsa (Yayasan Citra Cendekia Celebes, 2021)
Irrational use of drugs can harm society because it can lead to less effective treatment, the risk of side effects and the high cost of treatment. Irrational use of antibiotics can have serious consequences because they can lead to rapidly increasing bacterial resistance worldwide and cause significant morbidity and mortality. This study aims to determine the rationality of the use of antibiotics in pediatric inpatients and outpatients in hospitals using a literature review research type with the narrative review method. The results showed that there was still irrational use of antibiotics in hospitalized and outpatient pediatric patients.